Analysis and Interface Design on the UPT Website. Empowerment of Wilwatikta Arts Institutions and Creative Economy for Media Branding by Using the Goals Directed Design Method - Yusuf Ongky Alexsander; Anjik Sukmaaji; Sri Hariani Eko Wulandari (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
UPT. Institutional Empowerment and Creative Economy Wilwatikta is a high school of arts and culture located in Surabaya, East Java. UPT. Institutional Empowerment and Creative Economy Wilwatikta has a website that can be accessed at https://stkw-surabaya.ac.id/. During the Covid-19 pandemic, the need for services for students has increased. Until UPT. Empowerment of the Wilwatikta Arts Institute and Creative Economy considers it important to improve the website as a step to improve the quality of education, so that users can get information easily and efficiently, achieve the vision, mission and goals of the university, namely the website becomes one of the branding tools and introduces the university to the community in a holistic manner. Therefore, it is necessary to analyze and design the interface design or user interface on the website using the Goals Directed Design method, so that the website can be well received by users and provide user convenience in accessing the website. Based on the Goals Directed Design method for the research stage starting from observation, interviews and evaluation of the latest website, the modeling stage produces a user persona for website modeling, the requirements stage produces a website scenario context as a reference in designing the latest website prototype flow, the framework stage produces a website wireframe in the form of design recommendations for prototypes, the refinement stage produces a prototype website that can be used as a reference in making a new website so that it supports campus goals where the website is used as a branding medium and introduction to the general public, lastly there is a support stage there is prototype testing and final evaluation and analysis of test results, which yields a final mean of 3.7 (good). For the initial and final evaluation using usability testing and distributing questionnaires, where the usability testing stages consist of learnability, efficiency, memorability, errors and satisfaction.